COVID-19, Oil Prices and the US Policy Uncertainty - Claudiu Tiberiu ALBULESCU (Communications of International Proceedings, 2020)
This paper investigates the effect of COVID-19 and crude oil prices on the United States (US) economic policy uncertainty (EPU), with a focus on the pre-pandemic phase of the sanitary crisis. Using daily data for the period January 21 – March 13, 2020, our Autoregressive Distributed Lag (ARDL) model shows that the new infection cases reported at global level, and the fatality ratio, have no significant effect on the US EPU during the first phase of the crisis, whereas the oil price negative dynamics leads to increased uncertainty. However, analyzing the situation outside China, we discover that both new case announcements and the COVID-19 associated death ratio have a positive influence on the US EPU.
Keywords: COVID-19; Economic Policy Uncertainty; Oil Prices; ARDL Bound Testing.